Biocontrol efficacy of Lactobacillus fermentum YML014 against food spoilage moulds using the tomato puree model. Issue 1 (2nd January 2016) - Adedokun, Elizabeth O.; Rather, Irfan A.; Bajpai, Vivek K.; Park, Yong-Ha
ABSTRACT: Food-spoilage moulds are known for their destructive rot and for the production of carcinogenic metabolites such as mycotoxins. These metabolities play a major role in the deterioration of the quality and hygiene of foodstuffs, resulting in economic loss and posing a critical threat to livestock and human. The current study evaluates the antifungal activity of an isolate, Lactobacillus fermentum YML014 isolated from Nigerian fermented food (Cassava). YML014 showed strong antifungal activity against Aspergillus niger, Aspergillus flavus, Penicillium expansum and reduced the fungal mycelia by ∼50% while co-cultivating in liquid medium. The strain exhibited heat stability and showed antifungal activity over a wide pH range of 4.0–8.0. The strain was sensitive to all of the clinically important antibiotics used. The biopreservative potential of YML014 was evaluated using tomato puree. Mycelial growth of P. expansum was observed in the negative control after 3 and 25 days of incubation at 25°C and 4°C, respectively. The shelf life of tomato puree treated with YML014 was extended for 12 days at 25°C and 9 days at 4°C. The strong antifungal potential of YML014 against food-spoilage moulds suggests its ability as a potent food preservative agent.